Autobiographical Memory Specificity for Religious and Nonreligious Cues: A Comparison between Atheists, Christians, and Religiously Uncommitted People in Sweden - Hallin, Nathalie; Törnaeus, Paola; Mahmud, Wadad; Andersson, Gerhard (Journal for the Cognitive Science of Religion, 2020)
The aim of this study is to investigate religious autobiographical memories by having self-reported atheist, Christian, and religiously uncommitted Swedes perform the Autobiographical Memory Test (AMT) with added religious word blocks. The specific aims are to investigate (1) possible group differences in memory specificity, (2) whether positive or negative cue words evoked a larger number of specific memories, and (3) whether participants produced a larger number of specific memories in response to religious or nonreligious cue words. Sisty participants were included, with twenty in each group (atheists, uncommitted, and Christians). No group differences in memory specificity were found. However, positive and nonreligious cue words were associated with a larger number of specific memories. The possibility of using AMT to study cultural differences is discussed.